Employee Training and Development Strategies Using in House Training Method - Ilyas, Fadli; Oktaviani, Ayu (ProBisnis : Jurnal Manajemen, 2023)
Employees are an essential asset for a company. With employees, the company would operate at all. Therefore, sound resource management is needed, one of which is holding employee training. Bad management can have fatal consequences for a company if employees cannot do their work well. Then, many tasks will pile up and need to be completed quickly. Carrying out employee training will help employees to increase work productivity. This research was conducted to determine the employee training and Development form carried out at PT Panasonic Manufacturing Indonesia. Training and Development are critical in managing human resources in an institution, company, or organization. Human resources are an indicator of success for the survival of an organization or company. Hence, training and Development are essential for employees to increase their knowledge, skills, and abilities. Training provides specific knowledge and skills needed in the current job, while Development focuses on improving long-term knowledge, abilities, attitudes, and personality traits. Training is a process to improve employee abilities in specific jobs according to organizational needs and is carried out quickly. On the other hand, Development has a broader scope, aiming to prepare individuals to take on higher or different responsibilities in the organization. This second element is an investment in the organization, ensuring that employees have the skills necessary for effective and efficient performance. Analysis of employee training and Development (in-house training) for August – September 2023 at PT Panasonic Manufacturing Indonesia to provide an overview of employee performance at the company.